Développement durable, postures et responsabilité sociale des chercheurs en éducation - Angela Barthes; Jean-Marc Lange (Recherches en Éducation)
The article establishes the context of a new curricular construction, especially wich is the education for sustainable development (ESD). Building on a significant number of ESD research carried out in France, we establish a typology of postures of the researchers involved in this. This typology is constructed from a methodology based on occurrences of lexical frequencies of a bibliographic corpus coupled with a methodology of social representations of the researchers of this community. Six postures are built, which we named "acceptors", "descriptors / prescribers", "systemic", "controversy", "critical", "didactic". We postulate that these postures influence curriculum construction, questioning the social responsibility of educational researchers about an international political injunction.